Dietary fat, abdominal obesity and smoking modulate the relationship between plasma complement component 3 concentrations and metabolic syndrome risk - Mc Manus, Ross (My University, 2012)
Objective: Chronic inflammation plays a role in the pathogenesis of metabolic syndrome (MetS) and cardiovascular disease (CVD). Complement component 3 (C3) is a novel cardiometabolic risk factor. Whether dietary fat intake modulates MetS risk conferred by elevated C3 concentrations is unknown. Our objective is to investigate the relationship between C3 concentrations and risk of the MetS and its phenotypes, and to further examine whether dietary fat intake modulates these relationships. Methods: Biochemical, dietary and lifestyle measurements were determined in the LIPGENE-SU.VI.MAX study of MetS cases and matched controls (n = 1754). Results: Elevated C3 concentrations (> median) were associated with increased risk of impaired insulin sensitivity [OR 1.78, CI 1.34-2.36, P < 0.0001], insulin resistance [OR 1.73, CI 1.31-2.89, P = 0.0001], abdominal obesity [OR 2.15, CI 1.43-3.24, P = 0.0002] and low HDL cholesterol [OR 1.40, CI 1.05-1.86, P = 0.02] compared to low C3 concentrations. Increased MetS risk conferred by elevated C3 concentrations [OR 3.11, 95% CI 2.52-3.82, P < 0.0001] was further accentuated among high dietary fat consumers [OR 4.80, 95% CI 2.77-8.33, P < 0.0001] (particularly of saturated [OR 4.05, 95% CI 2.33-7.05, P < 0.0001] and monounsaturated fat [OR 4.48, 95% CI 2.62-7.56, P < 0.0001]), and smokers [OR 3.83, 95% CI 2.12-6.94, P < 0.0001], however this effect was abolished in abdominally lean individuals [OR 1.46, 95% CI 0.69-3.14, P = 0.33]. Conclusions: Dietary fat (intake and composition), abdominal obesity and smoking modulate the relationship between elevated plasma C3 concentrations and MetS risk.
PUBLISHED
Keywords: Clinical medicine; Metabolic syndrome; cardiovascular risk factors; Smoking; Obesity; Genes & Society; Immunology, Inflammation & Infection; International Development